Supporting students during the transition to university in COVID-19: Five key considerations and recommendations for educators. (March 2022) - Pownall, Madeleine; Harris, Richard; Blundell-Birtill, Pam
As coronavirus disease of 2019 (COVID-19) continues to disrupt pretertiary education provision and examinations in the United Kingdom, urgent consideration must be given to how best to support the 2021–2022 cohort of incoming undergraduate students to higher education. In this paper, we draw upon the "Five Sense of Student Success" model to highlight five key evidence-based, psychology-informed considerations that higher education educators should be attentive to when preparing for the next academic year. These include the challenge in helping students to reacclimatize to academic work following a period of prolonged educational disruption, supporting students to access the "hidden curriculum" of higher education, negotiating mental health consequences of COVID-19, and remaining sensitive to inequalities of educational provision that students have experienced as a result of COVID-19. We provide evidence-based, psychology-informed recommendations to each of these considerations.